Menelisik Putri Cina, Mengeluh Kesahkan Multikulturalisme - Heru Saputra (KAJIAN SASTRA, 2011)
This article aims to discuss the values of multiculturalism and social identity that is reflected in the Putri Cina novel by Sindhunata. The results show that the multicultural values appeared to start sowing by the author. Nevertheless, the people of Indonesia can’t be said as a multicultural society, because there are many cultural praxis that are not based on tolerance and equality. In addition, even during a binary opposition between the dominant and minority. In the Putri Cina novel reflected how the severity of the identity problem of discrimination in Indonesia, namely the Chinese in front of the Javanese. Sindhunata relatively cautious in criticizing the racial issue, through reflection the main character, so that dialogue is the projection of the embryo as well as the spirit of multiculturalism should not be done aloud. Nevertheless, the Putri Cina novel contains the embryo to criticize racial discrimination, with orientation on the fulfillment of the political attitude of the authorities and communities to adopt the attitude of equality. Keywords: multiculturalism, identity, ascriptive, Chinese, Javanese  http://ejournal.undip.ac.id/index.php/kajiansastra/article/view/2837